Design, synthesis, and biological evaluation of phenylisoxazole-based histone deacetylase inhibitors - Xiaofei Qin; Meng Han; Peng Hu; Huadong Que; Zhenlei Shao; Dong Yan (PLoS ONE, 2025)
Histone deacetylases (HDACs) mediate the removal of acetyl groups from lysine residues in both histone and non-histone proteins, and have been regarded as promising targets for drug discovery. As a central member of HDAC family, HDAC1 has been found to be closely linked to the occurrence and development of prostate cancer. In this study, we designed and synthesized a new series of 3-phenylisoxazole HDAC1 inhibitors based on the hit 7 , identified by in-house compound library screening. The structure-activity relationship studies (SARs) indicated that the R 1 position was relatively tolerated for activity. The linker length at R 2 exerted a significant influence on activity with the relative orders of butyl > propyl > ethyl > methyl. Among synthetic 16 compounds, compound 17 indicated the strongest HDAC1 inhibitory effect with the inhibition rate of 86.78% at the concentration of 1000 nM. In addition, derivative 17 could not only well occupy the active pocket of HDAC1, but also showed favorable drug-like properties. More importantly, molecule 17 exerted potent anti-proliferative activity on prostate cancer PC3 cells with the IC 50 value of 5.82 μM, and had no significant toxicity against normal prostate WPMY-1 cells. Collectively, these findings validate phenylisoxazole derivative 17 as a promising lead compound for further optimization and development.